Meta-Analytic Review of Dissonance-Based Eating Disorder Prevention Programs: Intervention, Participant, and Facilitator Features that Predict Larger Effects - Stice, Eric (Clin Psychol Rev, 2019)
Many trials have provided support for dissonance-based eating disorder prevention programs. This meta-analytic review characterized the average intervention effects and tested whether various intervention, participant, and facilitator features correlated with larger effects to guide implementation of optimally effective versions of this program. We identified 56 trials that evaluated 68 dissonance-based eating disorder prevention programs (7808 participants). Average intervention effect sizes (d) relative to minimal intervention control conditions and credible alternative interventions (respectively) were 0.57 and 0.31 for thin-ideal internalization, 0.42 and 0.18 for body dissatisfaction, 0.37 and 0.17 for dieting, 0.29 and 0.21 for negative affect, and 0.31 and 0.13 for eating disorder symptoms. As hypothesized, effects were larger for interventions with more dissonance-inducing activities, more group sessions, and larger group sizes, as well as when delivered in-person versus on-line, sessions were recorded, participation was voluntary, body dissatisfaction was required, participants were mid-adolescents or adults (versus older adolescence), there were more ethnic minority participants, groups were led by clinicians versus researchers and at least two facilitators, and when facilitators received more training and supervision. Unexpectedly from a dissonance-induction perspective, effects were larger when participants were compensated. Results offer directions for maximizing the benefits of implementation efforts with dissonance-based eating disorder prevention programs, and may hold lessons for preventing other public health problems with dissonance-based interventions.